PERATURAN PERPAJAKAN YANG BERKEADILANDAN BERKARAKTER SOSIAL KULTURAL BANGSA INDONESIA - Wahyudi Wahyudi (CV. Adiba Aisha Amira, 2023)
The policy principles in forming a tax law that is fair and has Indonesian cultural characteristics are described below. First, tax law provisions must be based on material truth, not formal truth. Second, tax law provisions must reduce the administrative burden on public administration, be simple, and easy to implement. Third, tax law provisions must use language that is easily understood and understood by the wider community. Fourth, the provisions of the tax law must quickly adapt to developments in information technology, economy, social and culture of society. Fifth, the provisions of the tax law must accommodate content materials that are the aspirations of the wider community. Sixth, tax law provisions must be in harmony with tax dispute decisions that have permanent legal force. Seventh, the formation of regulations must be carried out by law enforcers with integrity, professionalism, objectivity and independence